121k views
1 vote
The final step that will prove the length of hypotenuse c, squared that of each leg

The final step that will prove the length of hypotenuse c, squared that of each leg-example-1
User Shajin
by
5.7k points

2 Answers

5 votes

Answer:

It's the third choice.

Step-by-step explanation:

c^2 = 2a^2

Take square roots of both sides:

c = √2a

User Derjanb
by
6.3k points
1 vote

Answer:

It's the third choice.

Explanation:

c^2 = 2a^2

Take square roots of both sides:

c = √2a

User HarryQ
by
6.1k points